Analysis of The Influence of Work Life Balance on Employee Productivity PT United Tractors Tbk Tarakan Branch - Alysha Dzahabiyya Aurora Riyadi; Erlin Trisyulianti; Diki Akhwan Mulya (Jurnal Manajemen dan Organisasi, 2026)
Human resource management is a system that consists of various activities that are interconnected and do not run separately. PT. United Tractors Tbk, as one of the leading companies in the fields of heavy equipment, mining and construction, has shown a strong commitment to creating a conducive work environment and supporting a work-life balance of employees. This study aims to identify the perception of employees of PT. United Tractors Tbk Tarakan Branch about work life balance and employee productivity and analyzes the influence of the dimension of work life balance on employee productivity. The methods used are descriptive analysis and PLS analysis with SEM-PLS. The results of the study show that employees' perception of work-life balance and employee productivity is classified as a good criterion, then work-life balance affects employee productivity. It can be concluded that employees have the ability to distinguish and understand their positions and responsibilities at work, both in personal life and at work.